Assessing Liquefaction Risk at Timika Steam Power Plant through Cyclic Stress Ratio Analysis Using Borehole Data - Marsudi, Suwanto; Lufira, Rahmah Dara; Sajali, Muhammad Amar; Putra, Sebrian Bessely Mirdeklis; Asmaranto, Runi; Prasetyorini, Linda (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2025)
Energy infrastructure, particularly power plants, is critical in national and regional development. This study aims to determine the optimal placement and design of the Timika PLTU (power plant) by conducting comprehensive soil and rock investigations, focusing on seismic risks. The primary objective is to assess the geotechnical conditions of the site to ensure structural stability and safety in this high-seismicity zone. Key methods used in this study include borehole drilling, soil classification tests, and seismic hazard analysis. The soil at the site is classified as medium (SD) with Vs values ranging from 175 to 350 m/sec, and the seismic zone’s coefficient (Z) is 0.6, indicating significant seismic potential. The results reveal that specific design measures, such as sheet piles and retaining walls, are necessary to mitigate the risks of lateral collapse in areas with significant soil excavation. Furthermore, seismic design considerations were incorporated to improve the plant’s earthquake resistance. The findings of this study provide essential geotechnical data and practical recommendations, ensuring the safe and resilient construction of the PLTU Timika in a region prone to seismic activity while guiding future infrastructure projects in similar high-risk zones.